Consumer knowledge and opinion on selected sweeteners used in food. Part 2 - Rusek, Anna; Biazik, Ewa; Lesiów, Tomasz (Engineering Sciences And Technologies, 2017)
There are a growing number of sugar substitutes either allowed in food production or available on the market. The wide range of these substances might make consumer purchasing decisions harder. Therefore, the aim of this study was to evaluate Polish consumer knowledge of, and preferences for, the natural and synthetic sweeteners available on the market. This study presents the results of a survey of 186 consumers from Poland concerning consumer knowledge and opinions towards the consumption of selected sweeteners. The study showed that the majority of Polish consumers had insufficient knowledge about the use of different types of sugar substitutes and education in this area should be provided. The majority of respondents are not able to connect the name of sweeteners with their corresponding E symbols and are not willing to broaden their knowledge in this area. Moreover, 53% of respondents stated that sweeteners had a negative influence on health, and only 55% of responders believed that legally approved sweeteners were safe. Respondents were critical towards the application of sweeteners and were open to a change of habits in that respect, especially if it had a beneficial influence on their health
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies; 2017; Nr 1 (24); s. 62-73
Keywords: sugar replacers; sweeteners; consumer knowledge and opinions; zamienniki cukru; substancje słodzące; opinia konsumentów